Effects of lattice strain on hydrogen diffusion, trapping and escape in bcc iron from ab-initio calculations. (12th March 2023) - Luo, Fengping; Liu, Qingyuan; Huang, Jia; Xiao, Hao; Gao, Zhiying; Ge, Wei; Gao, Fei; Wang, Yugang; Wang, Chenxu
Abstract: Lattice strain potentially alters hydrogen (H) behaviors in structural materials and thus H-induced damages. Herein, we computationally investigate effects of lattice strain on H diffusion in the bulk region, and trapping by vacancy defects and escape in body-centered cubic (bcc) iron (Fe) using ab-initio calculations and statistical mechanics. The anisotropy of strain effect on H diffusion in bcc Fe is found in contrast with fcc systems, which essentially determines the alteration of H diffusion coefficient. The hydrostatic tensile strain attenuates H trapping, while the hydrostatic compressive strain inhibits H escape. The strong anisotropy of strain effect on H escape is confirmed, leading to low-barrier escape channels for H under the given anisotropic strain and facilitating H escape. This strong anisotropy is also reflected in the hopping of solute atoms He, C and O within 100 crystal planes. Strain effects on H trapping and escape become progressively more evident with decreasing temperature as shown by the escape rate. The obtained strain effects are in accordance with previous experimental observations on H in iron and steels under loading. Furthermore, the low-barrier channels of H escape from vacancy defects under strain are found to be the pathways where the density of electron gas is lower and the H-induced lattice distortion is weaker. The above results indicate a possibility of strain-promoted H-induced degradation of materials: strain-accelerated H transport from defects with low trapping depths for H to those with high trapping depths for H. This work also provides significant insights towards better understanding of H-isotope retention under strain in fusion reactors. Highlights: The strong anisotropy of strain effects on H diffusion, trapping and escape is revealed. The strain effects on H trapping and escape increase with decreasing temperature. Easier escape channels of H under strain are those with lower electron density and weaker H-induced lattice distortion. A possibility of strain-promoted H-induced materials degradation is suggested.